A ideia da fenomenologia em Michel Henry = The idea of phenomenology in Michel Henry - Praseres, Janilce Silva (Estudos teológicos, 2023)
Michel Henry (1922-2002), French philosopher and phenomenologist, who has a unique space in French-speaking philosophy, completed his centenary in 2022. 20 years have passed since his death. He was, without a doubt, an original thinker of a radical nature, responsible for proposing what we understand to be one of the most profound theories about subjectivity in the 20th century. Michel Henry also assumes an unusual position of understanding phenomenology in reference to its deepest question: the phenomenality of the phenomenon, its appearance as such, thus outlining a new path for phenomenology, the task of inverting it from within, proposing in this way a phenomenological inversion.